2017
DOI: 10.4208/jms.v50n2.17.01
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Prolate Spheroidal Wave Functions from the Perspective of Spectral Methods

Abstract: This paper is devoted to a review of the prolate spheroidal wave functions (PSWFs) and their variants from the viewpoint of spectral/spectral-element approximations using such functions as basis functions. We demonstrate the pros and cons over their polynomial counterparts, and put the emphasis on the construction of essential building blocks for efficient spectral algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…Theoretical aspects of the Mathieu functions have been studied by many authors, including Stratton [42], McLachlan [33], Sips [41], Meixner & Schäfke [34] and Wang and Zhang [45] (cf. also [44]).…”
Section: Introductionmentioning
confidence: 87%
“…Theoretical aspects of the Mathieu functions have been studied by many authors, including Stratton [42], McLachlan [33], Sips [41], Meixner & Schäfke [34] and Wang and Zhang [45] (cf. also [44]).…”
Section: Introductionmentioning
confidence: 87%
“…As recommended in [30,32], in practice, a quite safe choice is c = N 2 . With this in mind, we choose c = N 2 .…”
Section: Preliminariesmentioning
confidence: 99%
“…As we can see, the convergence is exponential and is almost indistinguishable for different c. Moreover, it is shown that the optimal c depends on the function being approximated [7]. In the following, we will take c = n/2 for general functions, which is recommended in [30,32]. 3 and 4.…”
Section: Numerical Testsmentioning
confidence: 99%
“…To the best of our knowledge, there are few reports for the spectral method of fourth‐order problems in circular domains. The main reason is that the polar transformation introduces singularity at the pole and the variable coefficients of the form r ± k [18, 19, 20], which brings some difficulties to implementation of the algorithm and error analysis.…”
Section: Introductionmentioning
confidence: 99%